Pentingnya Manajemen Sumber Daya Manusia dalam Meningkatkan Kinerja Organisasi - Adam Wahyu Satrio; Puji Isyanto (Global Leadership Organizational Research in Management, 2025)
Human resources have an important position in very organization because to achieve maximum organizational performance it is necessary to utilize its resources including human resources. Utilizing individuals in the organization to participate in maximizing organizational performance is the task of human resources manajement. This study aims to determine the importance of human resources manajement in improving organizational performance. This research use a qualitative approach with the miles and Huberman interactive analysis model. Qualitative data analysis is carried out interactively and continuously until completion, so that the data is saturated and consists of 3 main activities, namely: data reduction, data presentation, and conclusion drawing. Based on the research, the importance of human resource manajement (HRM) in improving organizational performance has been proven to be significant in the context of business ang manajement. HRM plays an important role in creating a healthy work culture, increasing employee motivation, and improving overall organizational productivity. By paying attention to factors such as transformational leadership, employee development, diversity management, and result-based performance management, HRM caan create an effective work environment and ensure that the organization has a qualified and high- performing work team, so that it can face businnes challenges, improve competitiveness, and achieve long-term success.